The Effectiveness Of Olanzapine And Diazepam Therapy In Schizophrenic Patients With Agitating States - Karsa, Nevi Sulvita; Lisal, Sonny T (State Islamic University of Sunan Ampel, 2024)
In the management of acute agitation in schizophrenia patients, the efficacy of antipsychotic medications, such as olanzapine has been widely studied. This study aimed to investigate the effectiveness of adding diazepam to olanzapine therapies in reducing agitation in schizophrenia. The research was conducted on a sample of patients diagnosed with schizophrenia in an agitated state. The study employed a pre-post-test design with non-randomized group selection, comprising two groups: olanzapine, olanzapine and diazepam. The Positive and Negative Syndrome Scale-Excited Component (PANSS-EC) was utilized to measure agitation symptoms. The results indicated a significant reduction in PANSS-EC scores in all groups from before therapy to the third day of therapy. In conclusion, combination therapy with antipsychotics and diazepam may be considered in the management of agitation in schizophrenia patients. Further research involving larger samples and exploring additional variables is recommended to enhance our understanding of this treatment approach.